China engages with the global intellectual property governance: The recent trend. (11th May 2019) - Cheng, Wenting
Abstract: As China becomes the second largest economy in the world, there have been increasing domestic demands requesting China to engage with the global governance of various issues more closely. In intellectual property (IP), China has recently engaged with global IP governance both responsively and actively. This paper answer the questions (a) how did China respond to the global IP up‐ratchet which sets higher IP standards; and (b) how did China actively promote its agenda for the global IP governance. This paper argues that China has a clearer and more consistent position in its responsive engagement than in active engagement. In other words, China is more affirmative in making defensive coalitions opposing TRIPS‐plus standards proposed by developed countries than promoting its own IP initiatives regionally or plurilaterally. China's positions in these defensive coalitions are the classic pro‐development, developing country positions. Its active IP engagement is more diversified. Specifically, China keeps a low profile and does not attempt to take the lead in IP negotiations at the Regional Compressive Economic Partnership. By contrast, China has emerged as a model exporter, focusing on IP capacity building in its IP arrangements in the Belt and Road Initiative (BRI) and BRICS.